2010
DOI: 10.1093/cercor/bhq244
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Impact of Ethanol on Cognitive Performance in Rhesus Macaques

Abstract: Decreased cognitive control over prepotent responses has been hypothesized to contribute to ethanol-induced behavioral disinhibition. However, the effects of ethanol on specific cognitive domains associated with decision making have not been extensively studied. We examined the impact of acute ethanol administration on cognitive performance of nonhuman primates. Studies were conducted using 0.2, 0.5, and 1 g/kg intravenous ethanol in rhesus macaques performing touch screen-based tasks examining stimulus discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 67 publications
5
24
3
Order By: Relevance
“…Results of the present study show that, in contrast to its effects on set-shifting, CIE exposure induced deficits in reversal learning that are similar to that reported for human alcoholics (Fortier et al, 2008; Fortier et al, 2009), primates (Jedema et al, 2010) and rodents (Brown et al, 2007; Obernier et al, 2002; Ripley et al, 2003; Thomas et al, 2004; Wainwright et al, 1990). That is, performance during reversal learning was significantly impaired following short-term abstinence from alcohol exposure, as CIE mice required more trials, made more errors and performed worse relative to simple discrimination (baseline) than controls.…”
Section: Discussionsupporting
confidence: 84%
“…Results of the present study show that, in contrast to its effects on set-shifting, CIE exposure induced deficits in reversal learning that are similar to that reported for human alcoholics (Fortier et al, 2008; Fortier et al, 2009), primates (Jedema et al, 2010) and rodents (Brown et al, 2007; Obernier et al, 2002; Ripley et al, 2003; Thomas et al, 2004; Wainwright et al, 1990). That is, performance during reversal learning was significantly impaired following short-term abstinence from alcohol exposure, as CIE mice required more trials, made more errors and performed worse relative to simple discrimination (baseline) than controls.…”
Section: Discussionsupporting
confidence: 84%
“…Acute exposure to ethanol disrupts reversal learning in monkeys (Jedema et al, 2011) and rats (Brown et al, 2007), and suppresses electrophysiological activity of lOFC neurons in mice (Badanich et al, 2013). Previous studies in our laboratory also demonstrate that mice exposed chronically to ethanol show impaired performance on a reversal learning task (Badanich et al, 2011) shown to require the lOFC (Bissonette et al, 2008).…”
Section: Introductionsupporting
confidence: 52%
“…In addition to manual responses, PES occurs after erroneous saccades (Endrass et al, 2007), and after responses made with the feet. PES is also observed across age-groups (Brooker and Buss, 2014; Friedman et al, 2009) and species (Jedema et al, 2011; Narayanan and Laubach, 2008). Theories of PES can be coarsely grouped into ‘adaptive’ theories, proposing that PES is aimed at improving ongoing behavior, and ‘maladaptive’ theories, proposing that PES signifies behavioral impairment caused by an error (for detailed reviews, see Danielmeier and Ullsperger, 2011; Ullsperger et al, 2014).…”
Section: Motor Slowing Following Unexpected Eventsmentioning
confidence: 91%